Experimental investigation on static and dynamic energy dissipation characteristics of composite sandwich structure with entangled metallic wire materials and disc springs - Yiwan Wu; Hu Cheng; Hongbai Bai; Shangzhou Li; Yu Tang (Materials Research Express, 2021)
In this paper, a novel composite sandwich structure with entangled metallic wire materials and disc springs (EMWM/DS) was proposed to improve the high temperature resistance and energy absorption characteristic of disc spring structure (DSS). The performance superiority of the proposed structure was verified by a series of quasi-static and low-velocity impact tests. On the one hand, the static energy dissipation characteristics of the EMWM/DS and DSS are compared through quasi-static test. Furthermore, the influences of the key experimental parameters and the densities of EMWM sandwich layers on the dynamic energy absorption characteristics of EMWM/DS are respectively studied by associating the mechanical properties of EMWM/DS with the helix wires based on curved cantilever beam of variable length. The experimental observations show that by increasing the density of the EMWM sandwich layer or increasing the compression deformation, the energy dissipation characteristics of EMWM/DS can be effectively enhanced. The composite sandwich structures still have good compression resistance and energy dissipation characteristics at high temperatures with increased environmental temperature. On the other hand, the dynamic energy absorption performance of the EMWM/DS and the DSS via low-velocity impact (LVI) is evaluated. The experimental results show that the complete impact energy absorption, specific energy absorption, and impact energy loss rate of the EMWM/DS can be increased by more than 93% compared with the DSS under the low-velocity impact (0.5 m s ^−1 –2 m s ^−1 ).